Impact of Lean Manufacturing Practices on Waiting Time of Patients in Outpatient Department (OPD): A Study in the Sri Lankan Public Healthcare Industry. - J. Thamilnila; SP Aryarathne, (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to explain the impact of lean manufacturing practices on waiting time of patients at the outpatient department (OPD) in the Public hospitals. Cross-sectional data using a survey sample of 384 patients in the Kandy public hospitals with a satisfied random sampling were used. Data were analyzed using SPSS software. This study covers the four independent variables of lean manufacturing practices namely: 5S, visual management, kaizen, and Just in Time. The dependent variable is waiting time. The measurement instrument for lean manufacturing practices and waiting time was developed from comprehensive literature reviews. Results indicate that there is a negative significant impact of lean manufacturing practices on waiting time of patients in outpatient department (Beta = -0.626 & p=0.000). Therefore, these findings suggest that the theories of lean manufacturing and the knowledge-based view providing implementation of lean manufacturing practices can reduce waiting time for patients in outpatient department.